2020
DOI: 10.21873/invivo.11913
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Algorithm in Hirschsprung's Disease: Focus on Immunohistochemistry Markers

Abstract: Background/Aim: Hirschsprung disease (HD) is caused by the congenital absence of ganglion cells in the distal bowel (aganglionosis). Rectal biopsy is considered important for its diagnosis. The aim of this study was to apply immunohistochemical staining using a minimal set of antibodies and develop an algorithm that will assist in the diagnosis of HD. Patients and Methods: Rectal or colonic biopsies were performed in patients with HD (n=26) or patients treated for other bowel diseases (n=34). Immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We previously showed that in case of congenital abdominal cystic lesions, a laparoscopically assisted minimal-access approach resulted in minimal risk of complications and complete recovery in all patients (17). On the other hand, a completely different approach was necessary for patients with Hirschsprung's disease (18).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that in case of congenital abdominal cystic lesions, a laparoscopically assisted minimal-access approach resulted in minimal risk of complications and complete recovery in all patients (17). On the other hand, a completely different approach was necessary for patients with Hirschsprung's disease (18).…”
Section: Discussionmentioning
confidence: 99%
“…The surgical resection length of aganglionosis was decided based upon the pathologist’s analysis of intraoperative fresh frozen biopsies taken by the pediatric surgeon, confirming the presence of ganglionic bowel wall. The accuracy of the frozen biopsy results was confirmed by full histopathological analyses by histopathological staining with hematoxylin–eosin and immunohistochemistry (calretinin and S-100) [ 16 , 17 , 18 ] in a final pathology report of the whole resected specimen.…”
Section: Methodsmentioning
confidence: 96%
“…Peripherin seems to be superior compared to calretinin and MAP-2 in ruling out HD in small biopsies [ 86 ]. Another study recommended the staining of calretinin and peripherin together in patients diagnosed with aganglionosis [ 87 ].…”
Section: Peripherin As a Marker Of Different Neuronal Populationsmentioning
confidence: 99%